Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 2001)
Table of Content Pictures and Score of Kaprow’s HOUSEHOLD by Philip Ursprung Tacita Dean Genius Loci by Jeremy Millar Sound as Duration in the Films of Tacita Dean by Paula Carabell Teignmouth Electron by Dieter Schwarz John Wesley Passive Expressive by Linda Morden A conversation about John Wesley by Kasper König & Marianne Stockebrand Débordement de vie by Bruce Hainley Thomas Demand Doubt the Day by Adrian Searle Memoryscapes by Andreas Ruby The Neutron Bomb Effect by Jörg Heiser Gerda Steiner & Jörg Lenzlinger, Insert Glen Wilson – Will the Circle Be Unbroken by Russell Ferguson The Veil of the Liminal. Mike Parr’s Brides by Edward A. Scheer Illuminations, The Drawings of Patti Smith, Les Infos du Paradis by David Greenberg San Keller: Art as a Public Service, Cumulus from Europe by Giovanni Carmine Incunabula, Cumulus from America by Steve Dietz
﻿“Delighted at making new friends, Gerda lifts them up and Jörg takes pictures of them.” This comment accompanies the photographs in our Insert, taken by Gerda Steiner and Jörg Lenzlinger on their journey around the world in 1998–1999. They are light-hearted pictures of people laughing in surprise at having just been lifted off the ground. “Lifting” has metaphorical implications and we notice that a simple, childlike, infectiously spontaneous act rises above cultural difference and the marks of conformity—and does so with disarming ease. (editorial by publisher)
boek
Keywords: Dean, Tacita; Wesley, John; Demand, Thomas